Respuesta :
Let the number is m
then:
one-sixth of a number = 1/6 m = m/6
and:
sum of one-sixth of a number and negative two = m/6 - 2
and:
sum of one-sixth of a number and negative two is equal to negative two-thirds : m/6 - 2 = -2/3
solving for m:
m/6 - 2 = -2/3
m/6 = -2/3 + 2
m/6 = 4/3 *6
m = 8
Your number is: six
Done
then:
one-sixth of a number = 1/6 m = m/6
and:
sum of one-sixth of a number and negative two = m/6 - 2
and:
sum of one-sixth of a number and negative two is equal to negative two-thirds : m/6 - 2 = -2/3
solving for m:
m/6 - 2 = -2/3
m/6 = -2/3 + 2
m/6 = 4/3 *6
m = 8
Your number is: six
Done
I hope that helps!
Answer:
[tex]\frac{1}{6}x+(-2)=-\frac{2}{3}[/tex]
Step-by-step explanation:
The sum of one-sixth of a number and negative two is equal to negative two-thirds.
LEt the unknown number be x
one -sixth is [tex]\frac{1}{6}[/tex]
one-sixth of a number is [tex]\frac{1}{6}x[/tex]
The sum of one-sixth of a number and negative two
Sum represents the addition, expression becomes [tex]\frac{1}{6}x+(-2)[/tex]
Now this expression is equal to negative two-thirds. [tex]-\frac{2}{3}[/tex]
The equation becomes
[tex]\frac{1}{6}x+(-2)=-\frac{2}{3}[/tex]